Relationship between Reading and Writing in English as a Second Language in the Context of Performance, Perceptions and Strategy Use - Ahmed Eldouma, Salaheldin Adam (2005)
This study investigated the relationship between reading and writing in terms of the performance, perception and strategy use of university ESL students. The subjects of the study were students of English language from the Faculty of Education at Sudan University of Science and Technology. The subjects attempted two reading tests and two writing tests to provide indicators of their performance that potentially reflected the reading and writing connection. They also responded to a structured questionnaire that investigated their perceptions about the connection between what they read and what they wrote to shed light on their affective responses towards the connection deemed important to foster language growth. From the subjects, 12 students were chosen based on the good readerlwriter and poor readerlwriter criterion and were asked to recall in writing two reading texts. They were also interviewed to investigate ESL learner strategy use in making this connection. The findings of the study showed that there was a relatively high degree of correlation between the students' reading and writing performance (r=O .741; p = .000). The findings also showed that the relationship between reading performance and writing performance differed according to the learners' levels of language proficiency which supports the bidirectional hypothesis. On the whole, the participants also showed positive attitudes towards integrating reading and writing skills. In response to the questionnaire, the students reported making connection between what they read and what they wrote by making notes/summary of what they had read, developing topics of their reading into paragraphs and using the main ideas of their reading texts to help them in their writing activities. However, the findings also showed that the culture of 'always-practising' good strategies appears to be underdeveloped among Sudanese tertiary students. Therefore, it is argued that further effort is needed on the part of instruction to help students improve the use of good reading and writing strategies. The analysis of the recall protocols also revealed that good writers recall better compared to good readers. Therefore, good writers are better readers in terms of recall compared to good readers. Accordingly, it is argued on the basis of the recall efforts that a good writer is more likely a better reader compared to a good reader being a better writer which further supports the results of the reading and writing performance tests as well as the analysis of the students' responses to the questionnaire. Furthermore, the students' interviews showed that all the interviewees practised some common strategies when reading and writing. Goodlpoor readers and goodlpoor writers prepared themselves for reading by checking the title and pictures first. However, good readers, poor readers and poor writers seemed to have similar plans for reading, whereas good writers had a clearer plan to approach reading (skimming for main ideas, scanning for details or reading the introduction first, among possible often strategies). There were however also no clear techniques used by the interviewees to generate ideas for their writing. The research shows a close connection between the constructs of reading and writing. It supports the contention that writing is generally the better indicator of reading ability. The findings point to work that can be done to nurture greater success in reading and writing abilities and to exploit the connections for the benefits of ESL language students.